Natural soundscapes in nature-based tourism: leisure participation and perceived constraints. Issue 4 (16th February 2020) - Jiang, Jinde; Zhang, Jie; Zheng, Chunhui; Zhang, Honglei; Zhang, Junyi
ABSTRACT: This study tries to verify the contribution of natural soundscapes to tourist satisfaction from the perspective of tourist participation and to reveal the constraint factors affecting tourist participation by using the leisure constraint model. The results indicate that tourists' participation in natural soundscape experiences significantly improves tourist satisfaction. There are five dimensions of participation constraints, and the 'individual activities' dimension is the most important constraint distinguishing participants from non-participants. The greatest constraint for both groups is 'lack of information, expectations and attraction'. The constraint forces faced by both groups are successively sorted into structural, interpersonal, and intrapersonal constraints. Knowing why tourists do not participate in natural soundscape experiences can suggest strategies that can be used to overcome constraints.